Need frustration and internet gaming disorder: The mediating role of gaming motivations - Goh, Ee-I; Ku, Yue Kei; Lee, Xin Qi (2023)
In view of the widespread multiplayer online battle arena (MOBA) as one of the most popular genres among all Internet games, Internet gaming disorder (IGD) could be developed due to addictive and excessive engagement in games. Therefore, drawing from the self determination theory (SDT), a cross-sectional study design was adopted in the present study to examine (1) the predictive effect of need frustration, intrinsic motivation, extrinsic motivation and amotivation on IGD and (2) the mediating effects of gaming motivations (i.e., intrinsic motivation, extrinsic motivation, and amotivation) on need frustration and IGD among Malaysian MOBA gamers. A total of 516 Malaysian participants ranged from aged 18 to 29 (M = 24 years), with at least one year of MOBA gaming experience, had recruited in the present study via purposive sampling method. The results revealed that need frustration, extrinsic motivation and amotivation were significant and positive predictors of IGD, but not intrinsic motivation. Concurrently, extrinsic motivation and amotivation were found to be mediating the association between need frustration and IGD. Nevertheless, intrinsic motivation was not a significant mediator. It was inferred that MOBA gamers whose basic psychological needs are being threatened might be drawn into a cycle of excessive gaming behaviours, culminating in IGD. The present study had contributed and provided more future research directions as there were limited studies conducted that focused on MOBA youth as well as the detrimental effect of need frustration on IGD in Malaysia. Concurrently, earlier prevention and intervention programmes should be practised via the focus of addressing the basic psychological needs, in order to promote healthy gaming behaviours among Malaysian youth Internet gamers.